2013
DOI: 10.3844/ajisp.2013.78.84
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Highly Purified De-Glycosylated Gcmaf in the Immunotherapy of Patients With Chronic Diseases

Abstract: The de-Glycosylated vitamin D binding protein is a powerful Macrophage Activating Factor (GcMAF) that shows multiple biological effects that could be exploited in the immunotherapy of tumours, viral infections and autism. Here we report the observation of a series of clinical cases describing the results obtained administering highly purified GcMAF to patients with diverse types of chronic diseases. These are heterogeneous and refer to patients with different types of diseases at different stages. In some case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Recent evidence, however, suggests that the therapeutic results observed with GcMAF are due not only to macrophage activation, but also to other direct effects of GcMAF on cell signalling and metabolism. We recently proposed that these effects may be explained considering the interconnection between GcMAF and VDR signalling pathways (Thyer et al, 2013b). The results presented in this study suggest a further interconnection with other signalling pathways that include ERK and NF-κB.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Recent evidence, however, suggests that the therapeutic results observed with GcMAF are due not only to macrophage activation, but also to other direct effects of GcMAF on cell signalling and metabolism. We recently proposed that these effects may be explained considering the interconnection between GcMAF and VDR signalling pathways (Thyer et al, 2013b). The results presented in this study suggest a further interconnection with other signalling pathways that include ERK and NF-κB.…”
Section: Discussionmentioning
confidence: 63%
“…These range from inhibition of angiogenesis (Pacini et al, 2011) to direct inhibition of human cancer cell proliferation and metastatic potential (Gregory et al, 2010;Pacini et al, 2012b) to increased production of energy at the mitochondrial level (Pacini et al, 2013). We recently demonstrated that these multifaceted effects of GcMAF can be interpreted considering the interconnection between the GcMAF and the Vitamin D Receptor (VDR) signalling pathways (Thyer et al, 2013b).…”
Section: Myalgicmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first example of actual images of tumor volume reduction following GcMAF immunotherapy. In effect, so far the effectiveness of immunotherapy of cancer with GcMAF has relied upon non-specific markers such as serum α-Nacetylgalactosaminidase levels (Yamamoto et al, 2008a;2008b;2008c;Thyer et al, 2013a) or anecdotic reports (Inui et al, 2013;Thyer et al, 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…The potent immunotherapeutic effects of GcMAF in human tumors have been demonstrated since 2007 in a variety of cancers ranging from the most common breast and prostate cancers to the less frequent oligodendroglioma (Yamamoto et al, 2008a;2008b;2008c;Inui et al, 2013;Thyer et al, 2013a;2013b).…”
Section: Introductionmentioning
confidence: 99%